Supervisor Leadership Style's Effect on Housekeeping Staff Performance at Makassar's Singgasana Hotel - Wulandari Pratiwi, Raden; Muhammad Salim, Muhammad Arfin; Islahuddin, Islahuddin (Jurnal Toursci, 2024)
A leader must engage with his subordinates using a leadership style. One of the components needed to support employee performance is this. This study aims to ascertain how the supervisor's leadership style impacts employee performance at the Singgasana Hotel in Makassar. Employee Performance is the research variable (Y), and the independent variable is the leadership style variable (X). This kind of study methodology is quantitative. The participants in this study were housekeeping staff members of the Singgasana Hotel in Makassar. In contrast, data analysis utilizing simple regression analysis was used to sample thirty employees who worked with up to thirty respondents by accidental sampling technique. Using the SPSS software version 22.0, a Likert scale-based questionnaire is used for data collection. According to research, leadership style positively and dramatically impacts employee performance at the Singgasana Hotel Makassar.